(3CPci GdfTQ aj GdeSGFd GdYTQs - (3eMeO aGd Hf eMeO Hf CMeO Hf eMeO GdYGbds ((3ehQjJGfjG s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hHYO agPg Led YTQ LeYgf GdabjQ Edi QHg GdeYJQa HGdLgd hGdbUhQ JeS GdMGLI Edjge ai Yde GdcdGe GdChdi MbjbI GdhMOGfjI Jai GdcKQI aMSH GdCLRGA hGdLRFjGJ aGdeQGO s
(3BNQgG (B:s
(3HEYJHGQ GdebGUO gh GdPi PgH Edjg GdMdjei hGHf eQRhb ai TQM GdHNGQi ceG ai GdCLhHI GdcHQi hjLH ZSd cGaQ HYO GdTgGOi HeG PcQGg s
(3HgG fXGe GdJYbjHIs
(3MhGagG ebUaI GdChQGbs
(3fSNI eYfhfI HGdMHQ GdCMeQ s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds